2018
DOI: 10.1080/09500340.2018.1517904
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for 4-laser white-light sources

Abstract: This paper describes a series of simulation experiments designed to demonstrate the feasibility of using solid-state lasers in white-light mixtures. The mixed-laser sources are evaluated in terms of the luminous efficacy of the radiation (LER) as well as different measures of colour performance. The latter include the CIE colour rendering index (R a) and the IES colour fidelity index (R f) as well as a selection of additional parameters in the two systems. Optimization of the mixtures is achieved by the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Table 4 summarizes the white light illumination performance of the experimentally implemented reflective cavity CM-LD and PC-LD white light sources in cool white (4000-5000 K) and daylight (5000-6000 K) color temperature ranges. In principle, LER of four lasers with yellow LD can be as high as 330 lm/W, 7,8 so the LEO could be as high as 200 lm/Wo with CRI >85 using our existing extended cavity prototype (with a light extraction efficiency of đťś‚ đť‘’đť‘Ą ~60%). Using more perfect DBR reflectors in the interior, đťś‚ đť‘’đť‘Ą ~80% could be achieved based on Table 3, and the LEO can potentially reach >260 lm/Wo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 4 summarizes the white light illumination performance of the experimentally implemented reflective cavity CM-LD and PC-LD white light sources in cool white (4000-5000 K) and daylight (5000-6000 K) color temperature ranges. In principle, LER of four lasers with yellow LD can be as high as 330 lm/W, 7,8 so the LEO could be as high as 200 lm/Wo with CRI >85 using our existing extended cavity prototype (with a light extraction efficiency of đťś‚ đť‘’đť‘Ą ~60%). Using more perfect DBR reflectors in the interior, đťś‚ đť‘’đť‘Ą ~80% could be achieved based on Table 3, and the LEO can potentially reach >260 lm/Wo.…”
Section: Discussionmentioning
confidence: 99%
“…4 Similar to LED lighting, the available architectures for LD-based light sources include phosphor conversion (PC) 5,6 and direct color-mixing (CM). 7,8 PC-LDs can achieve high color rendering index (CRI) and reduce the coherence-induced laser speckles by scattering the laser beam. 9,10 It has been applied to automobile lamplights, featuring 1000 times brightness with 30% energy saving compared to their LED counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our investigations in this field [28,32] were inspired by the work of Neumann et al [33] who successfully demonstrated a white-light 4-laser mixture with acceptable colour properties expressed in terms of the CRI and CQS metrics. Our earlier paper [28] also used CRI and CQS as measures of colour rendition.…”
Section: Optimisation Of Laser Diode Mixtures Using Tm-30-15 (Ies R F )mentioning
confidence: 99%
“…Our purpose in [32] was to optimise similar mixtures of solid-state lasers, and to utilize the more up-to-date method of the IES colour fidelity index R f [15,16].…”
Section: Optimisation Of Laser Diode Mixtures Using Tm-30-15 (Ies R F )mentioning
confidence: 99%